2021
DOI: 10.1002/lsm.23450
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of facial and non‐facial lentigines with a 730 nm picosecond titanium: Sapphire laser is safe and effective

Abstract: Objective: A 730 nm picosecond-domain laser was developed to improve the clearance of pigmented lesion and reduce adverse events. This study assessed the safety and efficacy of this system for the clearance of lentigines and explores how the short picosecond pulses interact with tissue via histology. Study Design and Methods: Twenty subjects with Fitzpatrick skin types II-IV were enrolled in this prospective, IRB-approved study. Four treatments were administered using a 730 nm picosecond-domain laser. Pre-and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
(91 reference statements)
0
12
0
Order By: Relevance
“…4 Compared with nanosecond pulses, picosecond pulses produce relatively more photomechanical effects over photothermal effects and achieve better confinement of thermal energy. 5 Rather than destruction of the entire cell as seen in high-fluence laser treatments, laser toning delivers enough energy to destroy the melanin granules within cells without damaging the entirety of the cell. 4 This leads to an overall reduction of melanin without triggering inflammation that could lead to a melasma exacerbation or hypopigmentation.…”
mentioning
confidence: 99%
“…4 Compared with nanosecond pulses, picosecond pulses produce relatively more photomechanical effects over photothermal effects and achieve better confinement of thermal energy. 5 Rather than destruction of the entire cell as seen in high-fluence laser treatments, laser toning delivers enough energy to destroy the melanin granules within cells without damaging the entirety of the cell. 4 This leads to an overall reduction of melanin without triggering inflammation that could lead to a melasma exacerbation or hypopigmentation.…”
mentioning
confidence: 99%
“…In fact, cases of patients with epidermal and dermal pigmented lesions successfully treated using 730-and 755-nm wavelength ps-laser devices have been reported. [4][5][6][7][8] With regard to the wavelength, a 785-nm wavelength exhibits a similar melanin absorption curve similar to that of 730-and 755-nm wavelengths. The effectiveness of treatment with a 785-nm ps-laser in removing multicolor tattoos and freckles has been reported.…”
Section: Discussionmentioning
confidence: 94%
“…Wavelengths of 730 and 755 nm exhibit higher selectivity for melanin pigments than wavelengths of 532 and 1064 nm. In fact, cases of patients with epidermal and dermal pigmented lesions successfully treated using 730‐ and 755‐nm wavelength ps‐laser devices have been reported 4–8 . With regard to the wavelength, a 785‐nm wavelength exhibits a similar melanin absorption curve similar to that of 730‐ and 755‐nm wavelengths.…”
Section: Discussionmentioning
confidence: 99%
“…All of these leaded to faster wound healing and absence of scar formation. Also, treatment of suchlike lesions with various laser-and light-based systems displayed less satisfactory results, [14][15][16] even with multiple sessions, [17][18][19] and different device combinations. 20 In a study performed on swine tissues, radio-wave surgery revealed less inflammatory response and smaller lateral thermal damage compared with CO 2 laser.…”
Section: Ta B L Ementioning
confidence: 99%